2009
DOI: 10.2337/dc09-1690
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor 7-Like 2 (TCF7L2) Polymorphism and Hyperglycemia in an Adult Italian Population-Based Cohort

Abstract: OBJECTIVETo assess whether TCF7L2 polymorphism has a role in the deterioration of glycemic control.RESEARCH DESIGN AND METHODSMetabolic variables were evaluated at baseline and after 6-year follow-up in 1,480 Caucasian subjects from a population-based cohort.RESULTSAt baseline, T-allele carriers showed significantly lower BMI and homeostasis model assessment for β-cell function (HOMA-B) values and higher fasting glycemia and diabetes prevalence. At follow-up, fasting glucose and HOMA-B index were increased and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…Other researchers have observed similar results for these and other glycemic and insulin traits 15,[41][42][43][44][45][46][47][48][49][50] and have also observed them in children. 51 The findings regarding β-cell function in individuals without T2D might be explained by the involvement of the TCF7L2 gene in the entero-insular axis, islet gene expression, and insulin secretion, 52 and although this gene does not increase the risk of obesity, its effect on T2D can be modulated by the BMI.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Other researchers have observed similar results for these and other glycemic and insulin traits 15,[41][42][43][44][45][46][47][48][49][50] and have also observed them in children. 51 The findings regarding β-cell function in individuals without T2D might be explained by the involvement of the TCF7L2 gene in the entero-insular axis, islet gene expression, and insulin secretion, 52 and although this gene does not increase the risk of obesity, its effect on T2D can be modulated by the BMI.…”
Section: Discussionsupporting
confidence: 76%
“…In individuals without diabetes, we found that rs12255372 in the TCF7L2 gene was associated with higher fasting glucose levels ( β = 2.05, P = .039) and less HOMA‐B ( β = −32.14, P = .025), independent of age, sex, and the presence of overweight or obesity. Other researchers have observed similar results for these and other glycemic and insulin traits and have also observed them in children . The findings regarding β‐cell function in individuals without T2D might be explained by the involvement of the TCF7L2 gene in the entero‐insular axis, islet gene expression, and insulin secretion, and although this gene does not increase the risk of obesity, its effect on T2D can be modulated by the BMI .…”
Section: Discussionsupporting
confidence: 67%
“…The same results were reported at Arabian population (Alsmadi et al, 2008) and Indian Pima population (Guo et al, 2007) that rs7903146 has low risk to type 2 DM (OR=1.04). In another study conducted in France population (Moczulski et al, 2007) and Italian population (Gambino et al, 2010) were reported different result that rs7903146 was a risk factor of type 2 DM.…”
Section: Discussionmentioning
confidence: 93%
“…Incidence of impaired fasting glucose and diabetes was almost twofold higher in homozygous carriers of the A allele. The results did not change significantly after adjusting for the genotype for TCF7L2 rs7903146, which is located 1.9 Mb downstream of ADRA2A [3] and which is the strongest candidate gene for Type 2 diabetes [6,8].…”
Section: Resultsmentioning
confidence: 99%